1989
DOI: 10.1111/j.1365-2842.1989.tb01312.x
|View full text |Cite
|
Sign up to set email alerts
|

Electromyographic studies of craniomandibular disorders: a review of the literature

Abstract: Craniomandibular disorders have been investigated from many points of view, structurally and functionally. To evaluate the behaviour of the masticatory muscles, electromyography (EMG) has been widely used and the studies have emanated from many different paradigms. The purpose of this paper is to review articles in which EMG has been used to study symptomatic subjects. Findings from sleep studies and basic laboratory studies seem to support the hypothesis of a correlation between masticatory muscle hyperactivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
6

Year Published

1993
1993
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 61 publications
1
50
0
6
Order By: Relevance
“…According to some studies 3,13,17 , TMD subjects present increased electromyographic (EMG) activity of masticatory muscles with the jaw at rest, i. e., closed lips with no teeth contact, and lower level of clenching electric activation. Some authors 11,16,19 also reported that, during mastication, subjects with TMD present activity in jaw-closing muscles (masseter and temporal muscles) during the opening phase, when they should be relaxed.…”
Section: Temporomandibular Disordersmentioning
confidence: 99%
“…According to some studies 3,13,17 , TMD subjects present increased electromyographic (EMG) activity of masticatory muscles with the jaw at rest, i. e., closed lips with no teeth contact, and lower level of clenching electric activation. Some authors 11,16,19 also reported that, during mastication, subjects with TMD present activity in jaw-closing muscles (masseter and temporal muscles) during the opening phase, when they should be relaxed.…”
Section: Temporomandibular Disordersmentioning
confidence: 99%
“…The electromyograph captures and amplifies action potentials of voluntary muscle contraction, providing additional diagnostic aid in evaluating neuromuscular system status 19 . Careful clinical examination is indispensable, and electromyography -if used judiciously -may assist in the comprehension of the electrical activity patterns of face and mastication muscles, providing care professionals with a more objective diagnosis and consequently a more effective approach to oral motor disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Other findings already correlated with whiplash and TMD in research studies, such as balance and postural abnormalities, shoulder-neckheadache, stress and psychosocial factors, parafunctional and adaptive habits, central mediated pain factors, and others, should be included as potential variables or descriptors to be defined in whiplash/TMD populations. [43][44][45][46][47] Limitations This article should be used within the context of a narrative literature review with its inherent limitations. A systematic literature review uses a strict methodology to answer a specific research question with specific outcomes, whereas a narrative review is better suited in addressing a broader range of questions and provides a summary of findings.…”
Section: Prognosis In Ptmd Patientsmentioning
confidence: 99%
“…Other indirect mechanisms may include postinjury stress, cervical postural changes, and postural imbalance. [43][44][45][46][47] These may be important considerations when evaluating and managing TMD.…”
Section: Mechanism Of Tmj Injury In Whiplash Traumamentioning
confidence: 99%